2020
DOI: 10.1186/s12889-020-8230-y
|View full text |Cite
|
Sign up to set email alerts
|

School ethos and adolescent gambling: a multilevel study of upper secondary schools in Stockholm, Sweden

Abstract: Background: Gambling is not uncommon among adolescents, and a non-trivial minority has serious problems with gambling. Therefore, enhanced knowledge about factors that may prevent against problematic gambling among youth is needed. Prior research has shown that a strong school ethos, which can be defined as a set of attitudes and values pervading at a school, is associated with a lower inclination among students to engage in various risk behaviours. Knowledge about the link between school ethos and adolescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
(52 reference statements)
2
12
0
1
Order By: Relevance
“…The findings corroborate and extend prior research which has shown that features of school effectiveness are associated with fewer health risk behaviours among the students [16,23,24]. The current study also extends the results of a prior publication based on the same data which showed that a school's level of teacher-rated ethos was inversely associated with student gambling and risk gambling [29], and thus indicates that features of school effectiveness at different levels of the school organisation may be relevant for students' inclination to engage in health risk behaviours.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The findings corroborate and extend prior research which has shown that features of school effectiveness are associated with fewer health risk behaviours among the students [16,23,24]. The current study also extends the results of a prior publication based on the same data which showed that a school's level of teacher-rated ethos was inversely associated with student gambling and risk gambling [29], and thus indicates that features of school effectiveness at different levels of the school organisation may be relevant for students' inclination to engage in health risk behaviours.…”
Section: Discussionsupporting
confidence: 89%
“…While the ambition of the current study has not been to explore the mechanisms at work between school leadership and student gambling and risk gambling, some plausible pathways can be derived on the basis of previous research. It is for instance reasonable to assume [21] that a strong school leadership may be reflected in a school's ethos, i.e., the attitudes, values and behaviours that characterise the social interaction among teachers and students and that are central in order to prevent the emergence of undesirable behaviours [22] including gambling and risk gambling [29]. Teachers' attitude to their students is a central component of the ethos concept [37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations